Impacto da recuperação renal na mortalidade intra e pós alta hospitalar - Paiva, Alberto Augusto Martins (2023)
Objective: To verify the impact of renal recovery on mortality in non-critically ill patients with acute kidney injury. Method: A prospective cohort study was carried out in a public hospital in the Federal District with patients with acute kidney injury admitted to a non-critical care unit. Renal recovery was assessed based on the ratio of serum creatinine to baseline creatinine and the patient was followed up for 6 months. Mortality was assessed during hospitalization and after discharge. Results: Of the 90 patients with hospital-acquired kidney injury, renal recovery was identified in 34.1% to 75% of cases, depending on the time of assessment, considering a follow-up period of up to 6 months. Recovery of renal function during follow-up had an impact on in-hospital mortality [95% CI 0.15 (0.003 – 0.73; p = 0019). Conclusion: Recovery of renal function has been shown to be a protective factor for mortality in patients admitted to the non-critical care unit. Early identification of kidney damage and monitoring of physiological and laboratory variables proved to be fundamental in identifying the severity of the disease and reducing mortality.